Pulmonary micro-tumor emboli resulting in paradoxical emboli: a case report. (February 2018) - Morin-Thibault, Louis-Vincent; Wiseman, Daniel; Fortin, Michelle; Couture, Christian; Provencher, Steeve
Pulmonary tumor embolism (PTE) is a rare manifestation of cancer. It is characterized by the presence of tumor cell emboli in the pulmonary arterioles and capillaries leading to an elevation of pulmonary vascular resistance. The ante-mortem diagnosis is difficult. We report a case of PTE associated with recurrent breast cancer that presented with neurological symptoms due to paradoxical cerebral embolism.